Design and performance evaluation of a multilayer fixed-bed binder-free desiccant dehumidifier for hybrid air-conditioning systems: Part II – Theoretical analysis - Hsu W.-L.; Paul S.; Shamim J.A.; Kitaoka K.; Daiguji H. (My University, 2025)
The interdependent physics involved in the transport, adsorption, and thermal phenomena within desiccant-based dehumidifiers makes the construction of theoretical models essential to investigate intrinsic mechanisms. In Part II of this series, a computational model is established that increases an understanding of transient mass and heat transfer phenomena in a multilayer fixed-bed binder-free desiccant dehumidifier (MFBDD). A two-dimensional (2D) model incorporating the principles of momentum, mass and heat conservation is constructed. A modification of Darcy's law is employed to evaluate the frictional resistance due to the presence of Micro Sphere Gel (M. S. Gel) beads in the desiccant bed. In the study, the moisture adsorption characteristics of M. S. Gel are theoretically described by employing a Linear Driving Force (LDF) model and a modified Langmuir-Sips model (based on the local relative humidity RH) owing to the unique sigmoid-shape of its adsorption isotherm at various temperature levels. The energy conservation is considered to estimate phase transition latent heat because of the moisture adsorption and heat loss to surroundings through the metal frames at different process air conditions. The validity of the model is tested by comparing the theoretical predictions with experimental observations. The results indicate that the predicted adsorbed water within the MFBDD, dehumidification capacity, temperature increase, and pressure decrease based on the simulation are in quantitative agreement with the experimental results obtained in Part I. The experimentally observed transient translocation of maximum temperature inside the M. S. Gel bed is theoretically reproduced and analyzed. © 2017 Elsevier Ltd